2021
DOI: 10.1109/lcsys.2020.3002852
|View full text |Cite
|
Sign up to set email alerts
|

Self-Configuring Robot Path Planning With Obstacle Avoidance via Deep Reinforcement Learning

Abstract: This work proposes a hybrid control methodology to achieve full body collision avoidance in anthropomorphic robot manipulators. The proposal improves classical motion planning algorithms by introducing a Deep Reinforcement Learning (DRL) approach trained ad hoc for performing obstacle avoidance, while achieving a reaching task in the operative space. More specifically, a switching mechanism is enabled whenever a condition of proximity to the obstacles is met, thus conferring to the dualmode architecture a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…After the simulation, the displacement, velocity, acceleration and force curve of the driving joint of each unit parallel mechanism module can be obtained as outputs. The simulation results are shown in Figures 8,9,10,11,12,13. where x, y, z, φ x , φ y , and φ z denote the position and orientation of the distal moving platform of the HRETR. By observing the kinematic diagram of Figures 8,9,10,11,12,13 the kinematic law of each limb meets the preset requirements (both the initial and terminal velocity and the acceleration are 0).…”
Section: Dynamic Analysis Of the Hretrmentioning
confidence: 99%
See 1 more Smart Citation
“…After the simulation, the displacement, velocity, acceleration and force curve of the driving joint of each unit parallel mechanism module can be obtained as outputs. The simulation results are shown in Figures 8,9,10,11,12,13. where x, y, z, φ x , φ y , and φ z denote the position and orientation of the distal moving platform of the HRETR. By observing the kinematic diagram of Figures 8,9,10,11,12,13 the kinematic law of each limb meets the preset requirements (both the initial and terminal velocity and the acceleration are 0).…”
Section: Dynamic Analysis Of the Hretrmentioning
confidence: 99%
“…With the introduction of the concept of Industry 4.0, robots have become more and more essential in intelligent manufacturing [1]. Despite the wide application of robots in the industry [2][3][4][5], medical sector [6][7][8][9][10], aerospace field [11,12], and other fields, consumers' needs are becoming increasingly dynamic and complex [13]. This challenge can be resolved with better motion flexibility, stiffness and load capacity of robots.…”
Section: Introductionmentioning
confidence: 99%
“…In [32] a dynamic obstacle avoidance approach for robot manipulator base on a continuous Deep-RL algorithm [33] was proposed and a well-designed reward function was presented to avoid the sparse reward and increase useful exploitation. In Sangiovanni et al [34], presented a hybrid control method that combines the Deep-RL policy and the PRM policy (i.e. a sampling-based method) to achieve collision-free path planning for anthropomorphic robot manipulators.…”
Section: Introductionmentioning
confidence: 99%
“…Between the tested approaches, the authors concluded that reusing experience improves performance greatly. Sangiovanni et al (2020) further extends the work in Sangiovanni et al (2018) by using a hybrid approach to the obstacle avoidance task, using conventional motion planning techniques and DRL. The idea is that if a metric evaluating the risk of collision is below a certain threshold, the system gives the control of the manipulator to a DRL system, which has the task of avoiding collisions.…”
Section: The Reward Functionmentioning
confidence: 89%
“…A video showing their experiments can be seen at <https://youtu.be/Zqc6sm76ZCg>. Sangiovanni et al (2018) proposes a system using DRL to perform motion control of a robot arm with obstacle avoidance. Their goal was to design a model that could be used in physical Human-Robot Interaction (pHRI), where the robot must avoid collisions with humans in its workspace.…”
Section: The Reward Functionmentioning
confidence: 99%